Laura Méndez de Cuenca (1853-1928), modern mexican in Europe and the United States: travel chronicles, literary contributions, pedagogical proposals - Arauz Mercado, Diana (Filanderas, 2022)
Laura Mendez, novelist, storyteller, poet and pedagogue, was lucky enough to practice her profession inside and outside the country at a time when it was not well seen for women to undertake trips or develop professional activities without interruption. Backed by the Mexican government, she traveled to several American and European cities, bequeathing to posterity more than 120 travel chronicles published between 1892 and 1910, in which she reflects the fact of traveling as a feminine vital necessity. In addition to this, she exchanged with her peers the various prevailing educational currents of that time under the idea of the efficacy of a North American educational system which stimulated the mystique for progress and pragmatic work from childhood. Mendez, drank from these and other foundations in her condition as a modern woman observing, pointing, rendering official and unofficial reports, controversial, while she became - on her returns to Mexico - one of the most brilliant figures of her time opening path to the first women within a nascent feminist thought, thanks to her numerous experiences and cultural exchanges.